AN OUTBREAK OF INFECTIOUS HEPATITIS IN A PRIVATE SCHOOL - K. Nasseri (Tehran University of Medical Sciences, 1977)
Between 15 October and 23 December 1975, a total of 22 cases of infectious hepatitis were reported from an upper class private school in the suburbs of Tehran. Careful examination revealed that one of the early cases had transmitted the disease to other children in the school during the last days of the incubation period.